2011
DOI: 10.1007/s12038-011-9061-x
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic consequences of misexpression of the developmentally active and stress-inducible non-coding hsrω gene in Drosophila

Abstract: The non-coding hsrω gene of Drosophila melanogaster is expressed in nearly all cell types and developmental stages. However, in the absence of conventional mutant alleles of this gene, its developmental functions remain largely unknown. In the present study, we used a variety of GAL4 drivers to overexpress or ablate this gene’s transcripts in specific tissues and examined the developmental consequences thereof. Our results show that a balanced expression of these non-coding transcripts is critical for survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 50 publications
1
26
0
Order By: Relevance
“…However, survival of a small proportion of eggs to the fertile adult stage, in spite of the hsrω-null condition or global RNAi is intriguing. To explain survival of the individuals with Act5C-GAL4-driven globally downregulated levels of hsrω transcripts, Mallik and Lakhotia (2011;also see, Lakhotia 2011) suggested that an as-yet unidentified "backup" machinery gets activated in the surviving individuals, which allows them to continue as weak individuals. We suggest that a proportion of the hsrω-null individuals likewise survive to adulthood at 24°C as weak individuals because their cells could developmentally adapt to the absence of omega speckles by successfully activating the presumed "backup" system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, survival of a small proportion of eggs to the fertile adult stage, in spite of the hsrω-null condition or global RNAi is intriguing. To explain survival of the individuals with Act5C-GAL4-driven globally downregulated levels of hsrω transcripts, Mallik and Lakhotia (2011;also see, Lakhotia 2011) suggested that an as-yet unidentified "backup" machinery gets activated in the surviving individuals, which allows them to continue as weak individuals. We suggest that a proportion of the hsrω-null individuals likewise survive to adulthood at 24°C as weak individuals because their cells could developmentally adapt to the absence of omega speckles by successfully activating the presumed "backup" system.…”
Section: Discussionmentioning
confidence: 99%
“…Among the various heatshock-induced genes in Drosophila melanogaster, the 93D or hsrω gene is unusual since, while it is developmentally active (Mukherjee and Lakhotia 1979;Bendena et al 1989Bendena et al , 1991Mutsuddi and Lakhotia 1995;Lakhotia et al 2001), it is singularly induced by amides and is also one of the most actively transcribed genes following heat shock (Mukherjee and Lakhotia 1979;Tapadia and Lakhotia 1997;Lakhotia and Tapadia 1998), although it does not code for any protein (Lakhotia and Mukherjee 1982;Garbe et al 1986;Lakhotia 2003). The hsrω gene produces multiple noncoding transcripts (Garbe et al 1986), of which the large (>10 kb) nucleus-limited hsrω-n transcripts organize the nucleoplasmic omega speckles (Prasanth et al 2000;Mallik and Lakhotia 2011), which sequester the various hnRNPs and certain other RNAprocessing proteins that are not actively engaged at a given time (Lakhotia et al 1999;Prasanth et al 2000;Jolly and Lakhotia 2006). Our recent studies (Mallik and Lakhotia 2009a, b, 2010, 2011Onorati et al 2011) have revealed that the hsrω RNA also affects, directly or indirectly, activities of DIAP1, CBP, JNK pathway, proteasome, ISWI, lamin C, etc., highlighting roles of these noncoding RNAs in multiple cellular networks (Lakhotia 2011).…”
Section: Introductionmentioning
confidence: 99%
“…[42][43][44][45][46][47][48] Similarly, lncRNA are shown to be involved in organization of heterochromatin, 38,41 paraspeckles, 39,49 nuclear stress bodies and multiple chromatin features. [50][51][52][53] In several other instances, lncRNAs act as guides for chromatin-modifying machinery and mediate the formation of a defined active/inactive chromatin compartment.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, loss of hsrω function causes the disorganization of omega speckles and a diffused distribution of hnRNPs in the nucleoplasm (Prasanth et al 2000;Lakhotia et al 2012;Mallik and Lakhotia 2011). Intriguingly, the heat-induced non-coding transcripts named Sat III identified in human cells display striking functional similarities with the fly hsrω transcripts (Jolly and Lakhotia 2006).…”
Section: Introductionmentioning
confidence: 99%